Guidelines for surveillance of individuals with constitutional mismatch repair-deficiency proposed by the European Consortium "Care for CMMR-D" (C4CMMR-D). Issue 5 (20th February 2014) - Vasen, H F A; Ghorbanoghli, Z; Bourdeaut, F; Cabaret, O; Caron, O; Duval, A; Entz-Werle, N; Goldberg, Y; Ilencikova, D; Kratz, C P; Lavoine, N; Loeffen, J; et al.
Abstract : Lynch syndrome (LS) is an autosomal dominant disorder caused by a defect in one of the DNA mismatch repair genes: MLH1, MSH2, MSH6 and PMS2 . In the last 15 years, an increasing number of patients have been described with biallelic mismatch repair gene mutations causing a syndrome referred to as 'constitutional mismatch repair-deficiency' (CMMR-D). The spectrum of cancers observed in this syndrome differs from that found in LS, as about half develop brain tumours, around half develop digestive tract cancers and a third develop haematological malignancies. Brain tumours and haematological malignancies are mainly diagnosed in the first decade of life, and colorectal cancer (CRC) and small bowel cancer in the second and third decades of life. Surveillance for CRC in patients with LS is very effective. Therefore, an important question is whether surveillance for the most common CMMR-D-associated cancers will also be effective. Recently, a new European consortium was established with the aim of improving care for patients with CMMR-D. At a workshop of this group held in Paris in June 2013, one of the issues addressed was the development of surveillance guidelines. In 1968, criteria were proposed by WHO that should be met prior to the implementation of screening programmes. These criteria were used to assess surveillance in CMMR-D. The evaluation showed that surveillance for CRC is the only part of the programme that largely complies with the WHO criteria. The values of all other suggested screening protocols are unknown. In particular, it is questionable whether surveillance for haematological malignancies improves the already favourable outcome for patients with these tumours. Based on the available knowledge and the discussions at the workshop, the European consortium proposed a surveillance protocol. Prospective collection of all results of the surveillance is needed to evaluate the effectiveness of the programme.